The Principles of Uti Possidetis Juris As an Alternative to Settlement Determination of Territorial Limits in the Oecusse Sacred Area (Study of the NKRI and RDTL Boundaries) - Dina Sunyowati; Haidar Adam; Ria Tri Vinata (Universitas Airlangga, 2019)
Based on the Decree of the People's Consultative Assembly in 1999, the legal status of the territory of Timor Leste is no longer the territory of the Unitary State of the Republic of Indonesia. With the establishment of the state of Timor Leste, between Indonesia and Timor Leste, boundaries of land and sea need to be included which cover territorial, ZEE and continental shelf boundaries, especially in the southern waters and north of the island of Timor, including the Oecusse enclave area. The negotiators of the two countries have not succeeded in agreeing on several Oecusse borderlines with the Indonesian territory. Various methods have been pursued including involving indigenous peoples. At present, the Oecusse enclave is designated as a special economic zone by Timor Leste with the aim of optimizing the area as a border area and having adequate economic activities so as to improve the quality of the local community. As an alternative effort in resolving regional boundary agreements, the application of the principle of Uti Possidetis Juris, which is a principle of territorial claims based on the Uti possidetis doctrine, means that a newly independent state inherits administrative boundaries formed by the previous authorities, so that the historical and conceptual approaches in the stipulation are established. It is recommended to avoid different interpretations between the two countries, and regional boundaries can be resolved immediately.